EXCAVATIONS AT THE DERBENT SETTLEMENT IN 2021 - Gadziev, Murtazali Serazutdinovic; Budajciev, Arsen Lahmanovic; Abdulaev, Abdula Magomedovic (History, Archeology and Ethnography of the Caucasus, 2024)
This paper presents the findings of the 2021 Derbent archaeological expedition at excavation area XXV, established in 2012 within the Derbent settlement dating from the 1st to 6th centuries AD. The excavations revealed upper layers 1 and 2, dating to the 5th-6th centuries AD, and fully uncovered rooms 10 and 11 of a housing and utility complex. Previous dating of this complex to the 5th – early 6th centuries was based on individual finds (chronological markers) and ceramic assemblages. The investigation determined that rooms 10 and 11 were originally a single rectangular space, later divided by a constructed wall that intersected a storage pit in the center of the original room. The room walls, composed of rubble and minimally processed stone with clay mortar, measure 45–55 cm in width and stand at a maximum preserved height of 68–95 cm. Wall 4, measuring 65–75 cm in thickness, serves as the eastern wall of room 10 and rooms 1–7. Extending 33 m, this outermost wall of the settlement is situated on a slope facing the Caspian Plain and likely served a defensive function. Room 10 (4.8 × 3.75 m) features a stone slab and rock pavement, suggesting a non-residential purpose. Room 11 (5.06 × 4.85 m) contains remnants of three wall-mounted clay ovens of the traditional two-chamber koryuk type, used for cooking food and baking bread. These ovens were located in a partitioned area with adjacent clay floors. The absence of clay flooring in the rest of room 11 indicates that small clay platforms were constructed in front of the ovens, while the remaining floor area consisted of leveled soil. The location of this excavation area in the southeastern part of the settlement holds significant promise for future investigations of the Derbent settlement, which predates Derbent founded in the late 560s.